Global analysis of oscillation parameters. (September 2019) - Capozzi, F.; Lisi, E.; Marrone, A.; Palazzo, A.
Abstract: We present an analysis of oscillation neutrino data in the standard framework of three massive and mixed neutrinos. The status of the known and unknown three-neutrino mass-mixing parameters is discussed. The main results of this work are that normal ordering (NO) is favored over inverted ordering (IO) at 3 σ level and that preferred values of the Dirac CP phase around nearly-maximal CP-violating cases. Finally, the octant of the atmospheric mixing angle remains undetermined.